Modification of the cartilaginous framework for autologous ear reconstruction: Construction of a stable complete ring framework with grander highs and lows. Issue 8 (August 2021) - Mazeed, Ahmed S.; O'Hara, Justine; Bulstrode, Neil W.
Summary: Background: Successful microtia reconstruction involves fabrication of a framework with well-defined ear subunits. Tragal definition and deep conchal bowl are key elements to produce a natural well-defined and contoured ear. We describe a modification in the cartilage framework with the purpose of increasing framework stability, tragal definition and conchal bowl depth. Methods: The tragus is placed on two cartilaginous bars (L-shaped), which are fixed to the framework base block creating a complete ring. These increase tragal projection and conchal depth. The tragus is carved angled posteriorly to have a shadowing effect on the absent auditory canal. Aesthetic outcome was assessed, at least 6 months after the second stage, on a 5-point ordinal scale (1–5) using the scoring system published in the UK microtia care standards and agreed on by the International Society for Auricular Reconstruction (ISAR). Results: A total of 406 auricular reconstructions were performed in 363 patients (206 right, 114 left, 43 bilateral). After excluding cases who did not have second stage and those without complete photographs, 290 cases were assessed. The described modification in the framework carving was performed in 255 ears out of these 290 ears. The mean aesthetic score before and after the modification was 2.4 and 3.09 respectively for the tragus ( p < 0.001), 2.2 and 2.95 for the intertragal notch ( p < 0.001) and 2.77 and 3.49 for the concha ( p < 0.001). Conclusions: This technical refinement has resulted in increased permanence and definition of the tragus and deeper and more aesthetic concha.